[OP.1A.08] PROGNOSTIC RELEVANCE OF RESTING HEART RATE IN OBESITY: LONGITUDINAL EVIDENCE FROM THE PAMELA STUDY. (September 2017) - Trevano, F. Quarti; Bombelli, M.; Facchetti, R.; Dell'Oro, R.; Boggioni, I.; Nicoli, F.; Peronio, M.; Re, A.; Mancia, G.; Grassi, G.
Abstract : Objective: We have previously shown that in the general population of the Pressioni Arteriose Monitorate E Loro Associazioni (PAMELA) study heart rate (HR) values fail to display a prognostic relevance for cardiovascular (CV) events, presumably because of the low risk profile of the overall population. In the present study we restricted the analysis to HR values in subjects affected by an obese state, i.e. a condition in which the detection of elevated HR values and an increased CV risk is common. Design and method: In 1944 subjects recruited in the PAMELA study and aged 51 ± 13.6 we measured at the study entry along with clinic, home and 24 hour blood pressure (BP), the corresponding HR values and waist circumference (WC). During the median follow-up period of 212 months we evaluated cardiovascular (CV) and total mortality. Data were analyzed subdividing the population in 3 gender specific tertiles of WC. Results: Compared to the lowest tertile, subjects in the highest tertile of WC displayed significantly greater clinic, home and 24 hour HR values. Focusing the analysis on subjects in the highest tertile of WC, after adjustment for gender, corresponding systolic BP and age, the risk of CV death was significantly greater with an increase of 1 bpm of home and 24 hour HR (hazard ratio 1.04 and 1.05, respectively, p < 0.05 for both), while no significant impact on CV mortality was found for clinic HR (hazard ratio 1.01, p = NS). The risk of all cause death was statistically significant for an increase of 1 bpm of clinic, home and 24 hour HR, after adjustment for confounders (hazard ratio 1.01, 1.023 and 1.039, p < 0.01 for all). Conclusions: HR, particularly when evaluated at home and during the 24 hours, represents an independent long-term predictor of fatal cardiovascular and non-cardiovascular events in patients with central obesity. For cardiovascular mortality, however, clinic HR does not appear to retain a prognostic value.